Factors that contributed to Congolese refugees and asylum seekers migrating out of Congo: The role of forgiveness. Issue 5 (4th July 2019) - Kandemiri, Pride; Nkomo, Thobeka S.
ABSTRACT: The purpose of this study was to explore the role of forgiveness on mental wellbeing interventions among Congolese refugees and asylum seekers. The study employed a qualitative research method and a descriptive case study of 10 female Congolese refugees living in Yeoville, Johannesburg South Africa. The participants have lived in South African for less than 5 years and there were 30–40 years of age. Data were collected by means of one-on-one in-depth interviews in the form of semi-structured interviews. Purposive sampling and snowball sampling techniques were used in the selection of participants. Thematic content analysis was used in analyzing the data collected. The findings of the study revealed that forgiveness plays an important role in mental wellbeing interventions. Forgiveness results in improved mental wellbeing with reduced anger, anxiety, depression, stress, and rumination. Participants who have forgiven the state forces and rebels reported that their mental wellbeing improved when they considered forgiving. This shows that there is a need to incorporate forgiveness in mental wellbeing interventions among Congolese refugees and asylum seekers.